PEMBELAJARAN BERCERITA DENGAN MODEL KOOPERATIF TIPE NUMBER HEAD TOGETHER DAN MEDIA BUKU DONGENG FABEL - Bambang Eko Supriyadi (MEDIA DIDAKTIKA, 2021)
The purpose of this study is to improve the ability to tell stories significantly through the use of cooperative model learning methods Number Number Together (NHT) in the form of fable fable books, which are expected to increase effectiveness, efficiency, and high attractiveness in providing a stimulus for students to dare to tell stories in front of the class or in the school environment. This study uses two data, namely quantitative data and qualitative data. From the results of the study it was obtained that the average post-test score was better than the pre-test which was 77.50> 29.59. whereas in the calculation of the manual t test with a significance level of 0.05, the results of t arithmetic tabel t table are 3.731> 1.717. meaning that Ho is rejected and Ha is accepted. So that there are significant differences in the learning media used. This shows that the learning methods and media used have high levels of validity qualifications, so the learning methods and media used are appropriate to be used and applied in learning.